The artistic-pedagogical residency as a space for critical training in Visual Arts: Interview with Neyde Joppert (Revista Apotheke, 2025)
This experience interview the relevance of artisticpedagogical residency in the context of teaching visual arts, considering initial training in visual arts. Discusses the process of recording and documenting pictorial processes, as a methodology for thinking and doing artistically. It presents an interview carried out in 2022, with artist professor Neyde Joppert (SP), during her participation in the Residency Artisticpedagogial project, created by Estúdio de Pintura Apotheke. It aims to contribute to a critical reflection on the teaching/learning processes in painting.
Keywords: teaching visual arts; documentation; artistic-pedagogical residency